Pancreatic Cancer Following Incident Diabetes in African Americans and Latinos: The Multiethnic Cohort. (18th June 2018) - Setiawan, Veronica Wendy; Stram, Daniel O; Porcel, Jacqueline; Chari, Suresh T; Maskarinec, Gertraud; Le Marchand, Loïc; Wilkens, Lynne R; Haiman, Christopher A; Pandol, Stephen J; Monroe, Kristine R
Abstract: Background: Diabetes has been proposed to be a risk factor for and a consequence of pancreatic cancer (PC). The relationship between recent-onset diabetes and PC is not well understood, and data in minorities are sparse. We examined the relationships between recent-onset diabetes and PC incidence in African Americans and Latinos in the Multiethnic Cohort. Methods: A total of 48 995 African Americans and Latinos without prior diabetes and cancer at baseline (1993–1996) were included in the study. Questionnaires, Medicare data, and California hospital discharge files were used to identify new diabetes diagnoses. Cox regressions were used to calculate hazard ratios (HRs) and 95% confidence intervals (CIs) for cancer associated with diabetes and with diabetes duration. Results: A total of 15 833 (32.3%) participants developed diabetes between baseline and 2013. A total of 408 incident PC cases were identified during follow-up. Diabetes was associated with PC (HRage75 = 2.39, 95% CI = 1.91 to 2.98). Individuals with recent-onset diabetes (within three or fewer years of PC diagnosis) had a greater risk compared with those with long-term diabetes across all ages. The HRage75 for recent-onset diabetes was 4.08 (95% CI = 2.76 to 6.03) in Latinos and 3.38 (95% CI = 2.30 to 4.98) in African Americans. Conclusions: Diabetes was associated with a more than twofold higher risk of PC in African Americans and Latinos, but recent-onset diabetes was associated with a 2.3-fold greater increase in risk of PC than long-standing diabetes. Our findings support the hypothesis that recent-onset diabetes is a manifestation of PC and that long-standing diabetes is a risk factor for this malignancy.